GEOGRAPHY TEACHERS’ UNDERSTANDING OF DEEP LEARNING PEDAGOGY IN THE MERDEKA BELAJAR CURRICULUM: A STUDY OF SENIOR HIGH SCHOOLS IN SURAKARTA - Gentur Adi Tjahjono; Chatarina Muryani; Singgih Prihadi; Albertus Erico Jerry Krisna Nugroho; Fitria Dewi Kartika (Universitas Sebelas Maret (UNS), 2026)
There is still a gap between the implementation of deep learning pedagogy in the Independent Curriculum and the pedagogical readiness of geography teachers in Surakarta City. This study examines geography teachers’ understanding of the deep learning approach within the implementation of the Merdeka Curriculum in Indonesian senior high schools. Deep learning is emphasised in the curriculum to promote meaningful, reflective, and critical learning; however, limited evidence exists regarding teachers’ pedagogical readiness. Using a mixed-methods embedded design, data were collected from 25 geography teachers in Surakarta City through questionnaires and focus group discussions. The study focused on four indicators: knowledge of deep learning concepts, implementation in classroom practice, perceptions of effectiveness, and professional development needs. The results indicate that 64% of teachers demonstrated a moderate understanding of deep learning, 24% showed high understanding, and 12% had low levels. While most teachers acknowledged the importance of deep learning and displayed enthusiasm, they faced challenges related to conceptual clarity, consistency in instructional practice, and limited institutional support. These findings suggest a gap between theoretical knowledge and actual implementation in geography education. The study underscores the need for structured professional development, collaborative learning communities, and contextual instructional design to enhance teacher capacity. This research contributes to the international discourse on curriculum reform by mapping teacher readiness and highlighting practical challenges in applying deep learning pedagogy within the Indonesian context.